Systemic Lupus Erythematosus presenting with Bullous lesion, Lupus Nephritis and Seizure - Sigdel, Mahseh Raj (Journal of Advances in Internal Medicine, 2013)
Development of bullous lesion is a rare cutaneous manifestation of systemic lupus erythematosus (SLE). Bullous eruptions in SLE are divided into three categories. Firstly, the lesions of SLE may blister. Secondly, a number of primarily blistering diseases have been associated with SLE.Thirdly, bullous SLE (BSLE), characterized bysub-epidermal blisters, IgG deposition at the dermoepidermal junction and autoantibodies against collagen VII, forms a distinct group. We report an18 years girl who met American College of Rheumatology diagnostic criteria for SLE presenting with bullous lesion and nephritis and developed seizure during the same admission. She had anti-nuclear antibody positive, anti-DsDNA antibody negative and serum complement, C3, level decreased. She was managed with steroid, hydroxychloroquine and cyclophosphamide to which her renal function improved significantly and the skin lesions remitted partially. We would also like to highlight the difficulties in establishing differential diagnoses of bullous lesion in SLE. Journal of Advances in Internal Medicine 2013;02(01):17-20 DOI: http://dx.doi.org/10.3126/jaim.v2i1.7633